Fruit and Vegetable Intake and Mortality: Results From 2 Prospective Cohort Studies of US Men and Women and a Meta-Analysis of 26 Cohort Studies - Wang, Dong D; Li, Yanping; Bhupathiraju, Shilpa N; Rosner, Bernard A; Sun, Qi; Giovannucci, Edward L; Rimm, Eric B; Manson, JoAnn E; Willett, Walter C; Stampfer, Meir J; Hu, Frank B (Circulation (New York, N.Y.), 2021)
The optimal intake levels of fruit and vegetables for maintaining long-term health are uncertain. We followed 66 719 women from the Nurses' Health Study (1984-2014) and 42 016 men from the Health Professionals Follow-up Study (1986-2014) who were free from cardiovascular disease (CVD), cancer, and diabetes at baseline. Diet was assessed using a validated semiquantitative food frequency questionnaire at baseline and updated every 2 to 4 years. We also conducted a dose-response meta-analysis, including results from our 2 cohorts and 24 other prospective cohort studies. We documented 33 898 deaths during the follow-up. After adjustment for known and suspected confounding variables and risk factors, we observed nonlinear inverse associations of fruit and vegetable intake with total mortality and cause-specific mortality attributable to cancer, CVD, and respiratory disease (all <0.001). Intake of ≈5 servings per day of fruit and vegetables, or 2 servings of fruit and 3 servings of vegetables, was associated with the lowest mortality, and above that level, higher intake was not associated with additional risk reduction. In comparison with the reference level (2 servings/d), daily intake of 5 servings of fruit and vegetables was associated with hazard ratios (95% CI) of 0.87 (0.85-0.90) for total mortality, 0.88 (0.83-0.94) for CVD mortality, 0.90 (0.86-0.95) for cancer mortality, and 0.65 (0.59-0.72) for respiratory disease mortality. The dose-response meta-analysis that included 145 015 deaths accrued in 1 892 885 participants yielded similar results (summary risk ratio of mortality for 5 servings/d=0.87 [95% CI, 0.85-0.88]; <0.001). Higher intakes of most subgroups of fruits and vegetables were associated with lower mortality, with the exception of starchy vegetables such as peas and corn. Intakes of fruit juices and potatoes were not associated with total and cause-specific mortality. Higher intakes of fruit and vegetables were associated with lower mortality; the risk reduction plateaued at ≈5 servings of fruit and vegetables per day. These findings support current dietary recommendations to increase intake of fruits and vegetables, but not fruit juices and potatoes.